Seduction, community, speech : a festschrift for Herman Parret - Parret, Herman; Brisard, Frank; Meeuwis, Michael; Vandenabeele, Bart (Pragmatics & beyond ;, 2004)
This volume unites various contributions reflecting the intellectual interests exhibited by Professor Herman Parret (Institute of Philosophy, Leuven), who has continued to observe, and often critically assess, ongoing developments in pragmatics throughout his career. In fact, Parret's contributions to philosophical and empirical/linguistic pragmatics present substantive proposals in the epistemics of communication, while simultaneously offering meta-comments on the ideological premises of extant pragmatic analyses. In a lengthy introduction, an overview is provided of his achievements in promo.